Acinetobacter baumannii: Identification, Antibiotic Sensitivity and Biofilm Formation in Different Clinical Samples (Bangladesh Journal of Medical Microbiology, 2018)
Background: Acinetobacter baumannii is responsible for nosocomial infections which are related to biofilm formation of this pathogen. Biofilm formation helps the bacteria in surviving stressed environmental conditions and bacteria growing in biofilms are resistant to most of the commonly used antibiotics. Objectives: The objective of this study was to detect A. baumannii, to see antibiotic sensitivity and biofilm formation in different clinical samples.Methods: Total 108 Acinetobacter spp. were collected from different clinical samples which were identified by conventional microbiological procedures. Out of 108 Acinetobacter spp, 85 were identified as A. baumannii by polymerase chain reaction by detecting blaOXA-51 gene which is intrinsic to A. baumannii. Antibiotic sensitivity was detected by modified disc diffusion method and biofilm formation was detected by Tissue culture plate method.Results: Among 85 isolates, 45.9% A. baumannii were obtained from tracheal aspirate followed by blood (21.2%), wound swab (15.3%), urine (10.6%), pus (5.9%) and pleural fluid (1.1%). More than 80% 0f A. baumannii was resistant to cephalosporin, aminoglycosides, quinolone, carbapenem. By Tissue culture plate method, 78.8% of isolates showed biofilm formation. Biofilm formation in tracheal aspirate was 82.1%, in blood 72%, in wound swab 92%, in urine 44.4%, in pus 100% and in pleural fluid 100%.Conclusion: Detection rate of A. baumannii was more in tracheal aspirates. Biofilm producing A. Baumannii was resistant to most of the antibiotics.Bangladesh J Med Microbiol 2018; 12 (2): 4-9